Influence of Self Efficacy and Quality of Work Life on Performance with Employee Engagement as a Mediating Variable - Amelia Ghita Atmawan; Alimuddin Rizal Rivai (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The purpose of this study is to analyze the effect of self-efficacy and quality of work life on employee performance with employee engagement as a mediating variable. This study uses a quantitative approach that emphasizes the analysis of numerical data processed by statistical methods. In this study, the population is employees at the Regional Secretariat of Semarang City, with as many as 165 employees and a sample size of 62 respondents. The primary data collection method used is by distributing questionnaires to respondents. The results of this study indicate that self-efficacy and quality of work life have a significant effect on employee engagement. Other influences on self-efficacy and quality of work-life variables do not affect employee performance; employee engagement has a significant impact on employee performance. In addition, the employee engagement variable can mediate the effect of self-efficacy on employee performance. At the same time, in the influence of a person's job fit and employee performance, employee engagement does not mediate the relationship.